Proceedings of 2015 2nd International Conference on Industrial Economics System and Industrial Security Engineering - Li, Menggang; Zhang, Qiusheng; Zhang, Juliang; Li, Yisong; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book collects high-quality papers on the latest fundamental advances in the state of the art and practice of industrial economics study and industrial security engineering, providing insights that address problems concerning the national economy, social development and economic security. The book is divided into major sections including Industrial Economics; Industrial Security; Empirical Studies; and others, all of which cover different aspects, such as industrial organization, industrial structure, industrial development, industrial distribution and industrial policies, as well as theories on industrial security in a globalized world. The papers in each section describe state-of-art research works that are often oriented on real-world applications, and highlight the benefits of related methods and techniques for developing the emerging fields of Industrial Economics and Industrial Security.
Part I Industrial Economics -- Part II Industrial Security -- Part III Empirical Studies -- Part IV Special Session on Cultural Industry -- Part V Special Session on National Economy -- Part VI Special Session on Finance Group -- Part VII Special Session on International Economics and Trade -- Part VIII Other.
Keywords: Industrial organization; Development economics; Economics; Economics; Industrial Organization; Development Economics; Economic Systems; Electronic books